Optimalisasi Dokumentasi Asuhan Keperawatan Berbasis Digital untuk Meningkatkan Kualitas Layanan di RS Panti Abdi Dharma Cirebon (Lembaga Pengembangan Kinerja Dosen, 2026)
Digital transformation in hospitals through the Digital Hospital concept (HIMSS EMRAM) aims to improve efficiency and reduce the potential for human error. RS Panti Abdi Dharma Cirebon has initiated the implementation of digital systems since 2015; however, several technical obstacles remain in its execution. Nurses, as the primary care providers, frequently face challenges in using electronic nursing documentation, which can negatively impact the quality of service and the continuity of patient care. This community service activity aims to enhance nurses' proficiency in using digital nursing documentation systems to support the improvement of healthcare quality and patient safety. The activity is conducted through three main steps: 1) Situational analysis and identification of technical constraints via questionnaires; 2) Technical training and coaching regarding the standardized structure of electronic nursing care documentation; 3) Evaluation of results by comparing the results/values of digital document completeness observations. Through this activity, a significant increase in nurses' knowledge and skills in operating the hospital information system is expected. It is also anticipated that there will be an improvement in the completeness of nursing care documentation, thereby minimizing medical risks and strengthening RS Panti Abdi Dharma's position towards national accreditation standards.